Psychiatric Care in Severe Obesity An Interdisciplinary Guide to Integrated Care - Sockalingam, Sanjeev; Hawa, Raed.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is designed to present a comprehensive, state-of the-art approach to assessing and managing bariatric surgery and psychosocial care. Unlike any other text, this book focuses on developing a biopsychosocial understanding of patients$1 (Bobesity journey and psychosocial factors contributing to their obesity and its management from an integrated perspective. Psychiatric Care in Severe Obesity takes a 360 approach by covering the disease$1 (Bs prevalence and relationship to psychiatric illness and social factors, including genetics, neurohormonal pathways and development factors for obesity. This book presents evidence and strategies for assessing psychiatric issues in severe obesity and uses common psychiatric presentations to feature the impact on bariatric surgery and key assessment features for weight loss. Concluding chapters focus on evidence-based psychosocial treatments for supporting patients with weight loss and bariatric surgery and includes educational tools and checklists for assessment, treatment, and care. Experts on non-pharmacological interventions such as mindfulness, cognitive-behavioral therapy and nutrition education describe treatment approaches in each modality, concluding with pharmacological approaches for psychiatric conditions and eating pathology. Additional tools in the appendices support clinicians, making this the ultimate guide for managing psychiatric illness in patients suffering from severe obesity. As obesity continues to grow in prevalence as a medically recognized epidemic, Psychiatric Care in Severe Obesity serves a vital resource to medical students, psychiatrists, psychologists, bariatric surgeons, primary care physicians, dietitians, mental health nurses, social workers, and all medical professionals working with severely obese patients.s
Introduction to Severe Obesity for Psychiatrists -- Severe Obesity: A Patient's Perspective -- Causes and Treatment of Obesity: From Genes to Integrated Care Models -- Causes of Severe Obesity: Gene to Environment -- Insecure Attachment and Trauma in Obesity and Bariatric Surgery -- Medical Complications Resulting from Severe Obesity -- Overview of Medical & Surgical Treatment of Severe Obesity -- Integrated Models for Severe Obesity Management: Role for Psychosocial Teams -- Weight-Based Stigma and Body Image in Severe Obesity -- Mood Disorders and Severe Obesity -- Eating Disorders in Severe Obesity -- Addictive Disorders in Severe Obesity and After Bariatric Surgery -- Sleep and Severe Obesity -- Psychiatric Suitability Assessment for Bariatric Surgery -- Nutrition Education for Severe Obesity -- The Role of Social Support in Weight Loss Management for Morbidly Obese Individuals -- Motivational Interviewing for Severe Obesity -- Mindful Eating for Severe Obesity -- Cognitive Behavioral Therapy for Severe Obesity -- Psychosocial/Behavioral Interventions in the Severely Mentally Ill -- Young Adulthood and Obesity Management: Developmental Issues and Transition of Care.-Technology to Promote Obesity Self-Management -- Pharmacological Treatment for Severe Obesity in Psychiatric Patients -- Psychopharmacology in Bariatric Surgery Patients -- Integrative Case and Summary.
Keywords: Medicine; General practice (Medicine).; Health promotion; Critical care medicine; Internal medicine; Psychiatry; Surgery; Medicine & Public Health; Psychiatry; General Practice / Family Medicine; Surgery; Internal medicine; Intensive / Critical Care Medicine; Health Promotion and Disease Prevention